Institutional bricolage: an approach to analyze the results of payment for environmental services in Chiapas, Mexico - Caballero Salinas, Juan Carlos; Vargas Vencis, Perla; Perevochtchikova, María (Instituto de Ecología, A.C., 2023)
Payment for environmental services (PES) were designed as market instruments that provide an economic incentive to forest landowners to conditionally ensure the provision of ecosystem services. Various investigations have shown that there is no consensus on its socio-environmental effects. Furthermore, little is known about the factors that influence the magnitude and directionality (positive/negative) of their results. Institutional bricolage is an approach that helps understand the results of public environmental policies, including PES. Bricolage occurs when the actors involved mix their own regulations, traditions, norms, and power relations that give rise to new institutional designs. Through ethnographic techniques, the concept of institutional bricolage is taken up to analyze the performance of the federal PES program in the ejido Tierra y Libertad, Jiquipilas, in the state of Chiapas. The field research revealed that the PES regulations were shaped at the local level by the bricoleurs (local actors) who made use of their attributes, agency, and power relations to adapt, reinterpret or reject the program regulations; this institutional change led to unforeseen socio-environmental results. Therefore, it is suggested to consider the local realities of territories where PES schemes are introduced, because in some socio-ecological contexts the regulations lack integration and acceptance in the norms and productive practices.